Planning, configuration and usefulness of microseismic monitoring on Eastern-Europe platform – example from east Pomerania - Kmieć, Mateusz; Antoszkiewicz, Michał; Szewczuk, Paweł; Szkodo, Marek; Jankowski, Robert (International Conference “Environmental Engineering”, 2017)
The microseismic monitoring is a method of monitoring of fracture propagation during hydraulic fracturing process. The method uses array of geophones to localize micro tremors induced by liquid pumped underground at high rate and pressure. The acquired information helps to optimize fracturing process and prevents fracture growth to aquifer levels. It was proved to be useful on several unconventional hydrocarbon reservoirs in the USA. Conducted investigation was aimed at evaluation of the possibility of using the technology on Polish unconventional reservoirs. In order to stand better chances of success the analysis of several variants of monitoring was made. East Pomerania geological structure was compared to similar structures in the USA. With this knowledge, financially feasible configuration was selected. The array of geophones was dispatched around the drilling site and data acquisition was performed. The present paper is mainly focus on geological structure, hardware selection, damping factor and noise level analysis. The usefulness of used receiver configuration is also assessed.
Keywords: Microseismic monitoring; noise analysis; hydraulic fracturing; detectability